THE IMPACT OF PERIPHERAL INTRAVENOUS (IV) CANNULATION IN THE AMBULANCE AND EMERGENCY DEPARTMENT. Issue 12 (18th November 2016) - Steel, M; Goodacre, S
Abstract : Objectives & Background: Intravenous cannulation in an emergency setting has significant potential benefits and harms to patients. Patients need to understand these in order to make an informed decision about cannulation. This research aims to improve knowledge and understanding of the benefits and harms of cannulation to patients, in addition to understanding the patient perspective of cannulation. Methods: Eighty patients were recruited from a convenience sample in a large urban academic emergency department (ED). Patients were included if they attended the department by ambulance and had a peripheral intravenous catheter inserted. Participants were asked to complete a questionnaire whilst they were attending the department. A follow up questionnaire was sent to the patients assessing the frequency of complications from cannulation. The number of attempts, proportion of catheters that go unused, rate of complications, symptoms associated with siting a cannula, patient understanding of cannulation and the patient perception of potential benefits and harms of cannulation were assessed. Results: The study population was 50% (40/80) male, with a mean age of 65 years and 72.5% (58/80) had their cannula inserted in the ED; the remainder were inserted in the ambulance (22/80). Cannulae were used 60% (CI 51.4%–68.6%) of the time, cannulae inserted in the ambulance were much more likely to be used than those inserted in the ED, 92% vs 48%, p<0.001. Some 21.3% (CI 13.8%–28.8%) of patients did not know why they had a cannula inserted. Not knowing why the cannula was inserted was not associated with anxiety levels (p=0.415). Mean pain score (Likert 0–10 scale) was 1.66 (CI 1.21–2.12). Patients who underwent multiple attempts reported higher pain score, 3.45 vs 1.38 (p=0.020). Only 26.6% (CI 19%–35.4%) of patients were told the risks of cannulation but 88.8% (CI 82.5%–93.8%) of patients believed insertion of the cannula was important. Conclusion: The majority of patients have an understanding of the purpose of cannulation, with the majority of patients believing cannulation is important in emergency care. However patients are not frequently told the potential risks of cannulation and would like to be told these. Cannulae inserted in the emergency department are not frequently used and efforts should be made to reduce the number of cannulae inserted but then not used.